2021
DOI: 10.3389/fpls.2021.715289
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Biochemical Analysis Reveal Integrative Pathways Between Carbon and Nitrogen Metabolism in Guzmania monostachia (Bromeliaceae) Under Drought

Abstract: Most epiphytes are found in low-nutrient environments with an intermittent water supply. To deal with water limitation, many bromeliads perform crassulacean acid metabolism (CAM), such as Guzmania monostachia, which shifts from C3 to CAM and can recycle CO2 from the respiration while stomata remain closed during daytime and nighttime (CAM-idling mode). Since the absorbing leaf trichomes can be in contact with organic (urea) and inorganic nutrients (NO3−, NH4+) and the urea hydrolysis releases NH4+ and CO2, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Water may be the chief limiting factor for tropical epiphytes such as bromeliads (Zotz and Bader, 2009; Males, 2016), particularly as episodes of drought increase in frequency and duration due to global warming (Colwell et al, 2008; Corlett, 2016), but the relative scarcity of mineral nutrients in the canopy also requires special adaptations (Zotz, 2016). For example, aquaporins in the leaves of the bromeliads Vriesea gigantea and G. monostachia can take up urea and other organic forms of nitrogen from the tank (Matiz et al, 2019; Gonçalves and Mercier, 2021), and several species have been shown to obtain mineral N through their association with decomposing microbes and N‐fixing cyanobacteria (Bermudes and Benzing, 1991; Inselsbacher et al, 2007). Phosphorus may be even more limiting than N for tank bromeliads, which have numerous biochemical adaptations to improve P‐uptake and storage (Winkler and Zotz, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Water may be the chief limiting factor for tropical epiphytes such as bromeliads (Zotz and Bader, 2009; Males, 2016), particularly as episodes of drought increase in frequency and duration due to global warming (Colwell et al, 2008; Corlett, 2016), but the relative scarcity of mineral nutrients in the canopy also requires special adaptations (Zotz, 2016). For example, aquaporins in the leaves of the bromeliads Vriesea gigantea and G. monostachia can take up urea and other organic forms of nitrogen from the tank (Matiz et al, 2019; Gonçalves and Mercier, 2021), and several species have been shown to obtain mineral N through their association with decomposing microbes and N‐fixing cyanobacteria (Bermudes and Benzing, 1991; Inselsbacher et al, 2007). Phosphorus may be even more limiting than N for tank bromeliads, which have numerous biochemical adaptations to improve P‐uptake and storage (Winkler and Zotz, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the best‐studied adaptation to a limited and variable water supply is the wide range of water‐conserving CAM photosynthetic pathways shown in the group, from full CAM to weak CAM, including the C 3 –CAM intermediacy of the focal species in this study, G. monostachia (Smith et al, 1986 ; Maxwell et al, 1994 ; Crayn et al, 2015 ; Pikart et al, 2020 ). Adaptations to limited mineral nutrients include high‐affinity membrane transporters for nitrogen (Inselsbacher et al, 2007 ), phosphorus (Winkler and Zotz, 2009 ), and potassium (Winkler and Zotz, 2010 ), and the capacity to acquire organic sources of N such as urea (Matiz et al, 2019 ; Gonçalves and Mercier, 2021 ). The most fundamental adaptation to limitation of both water and nutrients may be the slow growth rate of most epiphytes, including tank bromeliads (Schmidt and Zotz, 2002 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the leaves of another facultative bromeliad Guzmania monostachia, increases in the expression of CAM-related genes (PEPC1, PPCK, NAD-malate dehydrogenase, aluminum-activated malate transporter 9 (ALMT9), PEP carboxykinase (PEPCK)) and UREASE transcripts were shown under drought. And the role of integrating N and C metabolism of urea was suggested [78]. The CAM gene expression, antioxidant activities, and chlorophyll fluorescence were compared between a C 3 -CAM facultative species (Sedum album) and a C 4 -CAM facultative species (Portulaca oleracea) [79].…”
Section: Studies On C 3 To Cam Transition Revealed Important Molecula...mentioning
confidence: 99%